Global value added chains and the recruitment activities of European professional football teams - Velema, T. A.; Wen, H.-Y.; Zhou, Y.-K. (International Review for the Sociology of Sport, 2020)
This paper examines where European professional teams recruit new players in order to shed light on the functioning of global value added chains in world football. Most studies either point to the increasing internationalization of football`s labor force to argue that European clubs recruit from peripheral but culturally or historically related countries or turn to the experiences of players with domestic transfers to suggest that most teams recruit within their country. This study directly examines the recruitment activities of teams active in the highest two leagues of Europe`s top seven countries between the 2003/2004 season and the 2011/2012 season. Results indicate that even though Europe`s football labor force looks internationalized at first sight, many international players hold dual nationality and might be more aptly characterized as domestic players who are members of the large immigrant communities who came to Europe after the de-colonization of former colonies or as part of the stream of labor migrants in the 1960s and 1970s. Moreover, for most teams, domestic mobility forms the backbone of their recruitment activities, but some teams, especially in Portugal, buy football talent from teams in the global South and sell their best players to larger European teams. These results urge researchers to reconsider teams as more myopic and geographically bounded actors in global value added chains, incorporate domestic mobility into global value added chains, reconsider what counts as the core and the (semi-)periphery connected through the chains, and be wary of approaches taking countries or even leagues as the basic unit of analysis in global value added chains.